Oxygen Reduction on Carbon-Supported Metallophthalocyanines and Metalloporphyrins - Zagal-Moya, J; Zagal-Moya, J; Muñoz-Becerra, K; Muñoz-Becerra, K; Venegas-Toledo, R (Elsevier, 2018)
MN4 macrocyclic metal complexes have been studied for many years as potential catalysts for the O2 reduction reaction (ORR) in order to replace costly Pt and Pt group metals from the cathode of fuel cells. These macrocyclic complexes lack the necessary stability over long periods of time required for fuel cell operation especially in acidic electrolytes. However, they have provided very good models for establishing reactivity descriptors. The activity plotted with the M-O binding energy describes a volcano correlation. For Mn and Fe complexes, the onset for ORR occurs at potentials very close to the M(III)/(II) redox potential of the complexes in contrast to Co complexes. In general, the more positive the M(III)/(II) redox potential, the highest the activity. This is also true for MN4 catalysts dispersed on carbon nanotubes using different strategies. MNx catalysts obtained by pyrolysis of MN4 complexes show higher activity and stability and are more promising for fuel cell applications. The M(III)/(II) transition is a reactivity descriptor for these materials as observed for intact MN4 complexes. © 2018 Elsevier Inc. All rights reserved.